Rancang Bangun Sistem Perizinan Santri Dengan RFID Berbasis Internet of Things Untuk Ponpes Nurul Huda Setu Cikarageman - Hafiz Fachreza; Rully Pramudita (Jurnal Ilmiah Informatika Global, 2026)
The management of student permissions in Islamic boarding schools is commonly carried out through manual recording, which often creates problems such as inefficient administration, data loss, delays in monitoring, and limited parental involvement. To address these issues, this research designed and implemented an Internet of Things (IoT)-based permission system by combining Radio Frequency Identification (RFID), an ESP32 microcontroller, and WhatsApp API for real-time communication. The study applied the prototyping method, consisting of requirement analysis, system design, prototyping, alpha and beta testing, and final implementation. The proposed system allows students to scan an RFID card to request permission, automatically records the data into a MySQL database integrated with a CodeIgniter-based web application, and immediately sends notification messages to parents via WhatsApp. Implementation results show that the system successfully recognizes RFID input, stores transaction data consistently, and transmits notifications reliably. Alpha testing achieved a success rate of 98% across multiple test scenarios, while beta testing conducted at Pondok Pesantren Nurul Huda indicated that administrators, students, and parents considered the system more efficient, accurate, and transparent compared to manual methods. This research demonstrates the potential of IoT to improve administrative processes and enhance supervision in educational institutions.